Peran Kegiatan Ekstrakulikuler Pramuka dalam Membentuk Karakter Disiplin Siswa-Siswi Kelas XII MA. Al-Muhtadi - Jimly Assidqi; Sutopo Sutopo (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2020)
Character is currently a topic that needs to be discussed in education, especially the character of discipline. Character is believed to be an important aspect in improving the quality of Human Resources (HR), because character also determines the progress and setbacks of a nation. The formulation of the problem taken is: How is the process of implementing scout extracurricular activities in shaping the disciplined character of class XII students at MA Almuhtadi. How is the role of scout extracurricular activities in shaping the disciplined character of class XII students at MA Almuhtadi. What are the factors that influence the implementation of scout extracurricular activities in shaping the disciplined character of class XII students at MA Almuhtadi. The research objectives are: To know how the process of implementing scout extracurricular activities in shaping the discipline character of class XII students at MA Almuhtadi. Knowing how the role of scout extracurricular activities in shaping the discipline character of class XII students at MA Almuhtadi.Lamongan. Knowing what factors influence the implementation of scout extracurricular activities in shaping the disciplined character of class XII students at MA Almuhtadi. This thesis uses a qualitative research type, which produces data and is analyzed using a case study method and then described descriptively. The data collected using interview, observation and documentation techniques. The results of this study are: 1. The process of implementing scout extracurricular activities in shaping the disciplined character of students in the following ways: exemplary, habituation, advice/direction, and warning/punishment. 2. The role of extracurricular activities in shaping the character of discipline is very large. The importance of implementing scout extracurricular activities in every school in shaping the disciplined character of students. The role of scout extracurricular activities in shaping the disciplined character of students at MA Almuhtadi is manifested in the form of time discipline, discipline in enforcing rules, discipline in attitude, and discipline in worship. 3. Supporting factors are internal factors, namely from the student's self-will. And external factors, namely from the coach, and from a supportive family environment. the inhibiting factor is an internal factor, namely from the student's self-will. And external factors, namely from the family environment, and the development of the times that are not supportive.